Social and non-social directional cues differentially orient attention by learned habit - Salera, Claudia; Yankouskaya, Ala; Petrucci, Manuel; Pecchinenda, Anna (Frontiers in Human Neuroscience, 2025)
IntroductionSince an early age, we are implicitly motivated to use the direction of eye gaze of others to learn about the environment, and we orient our attention in space based on this directional signal. Similarly, we orient our attention based on the direction of arrow signs. In both cases, the mechanisms underlying attentional orienting rely on the activity of brain areas involved in endogenous attention; however, orienting by gaze direction also relies on brain areas involved in exogenous attention.Research questionsTo date, it remains unclear whether the acquisition of attentional habit, which can also guide attention in ways that are not purely endogenous or exogenous, is similar for gaze and arrow or rather differs in some important way. We aimed to assess whether learning implicit regularities implemented with exogenous, arrow, and gaze stimuli guides attention in space.MethodsUsing the Posner paradigm, we conducted a series of behavioral experiments with exogenous, arrow, and gaze cues. Unbeknownst to participants, specific regularities, namely cue predictive validity and probability cueing, were implemented through blocks (baseline, learning, testing).Results and discussionThe findings showed that predictive validity alone is not sufficient to engender habitual attention for all types of cues. However, it becomes effective when combined with probability cueing. Importantly, a learned habit with gaze cues engenders unique effects on attention compared to other cues.ConclusionSocially relevant directional signals, such as gaze, can bias spatial attention more effectively than perceptual or non-social directional stimuli.